EDUKASI PEMILAHAN SAMPAH MELALUI MEDIA PROMOSI DAN SOSIALISASI SEBAGAI UPAYA OPTIMALISASI PERAN TPS3R DI DESA TELUKJAMBE - Bunga, Venny Ulya; Umam, Hilman Imadul; Pambudi, Teguh (Universitas Mataram, 2024)
Waste management systems like TPS3R are critical for reducing, utilizing, and managing trash at its source. However, the TPS3R presence in Telukjambe Village has not been perceived as effective in conducting waste management as required. One major issue with the TPS3R's insufficient waste management is the unsegregated waste entering the facility, which is caused by the nearby locals' lack of understanding about domestic waste sorting. Therefore, it is imperative to implement initiatives aimed at enhancing knowledge and concern about waste separation among the people surrounding the TPS3R in Telukjambe Village. We implement educational campaigns on waste separation through door-to-door outreach, where representatives visit residents' homes to provide technical information on home-based waste sorting using diverse educational media. Furthermore, to improve understanding of waste sorting and TPS3R management, we conducted socialization by inviting speakers to deliver the information in an engaging and participatory manner. The evaluation results indicate that around 82.4% of respondents, specifically those living there, answered the waste sorting questions accurately. The locals possess a solid comprehension of garbage sorting, providing a robust platform for increased participation in household waste segregation. Furthermore, the local government's role in establishing legislation for household trash segregation and TPS3R management can guarantee the sustainability of current initiatives, ensuring their continued implementation.